PENINGKATAN PRODUKTIVITAS PEMASARAN YAMNI HONEY DENGAN PENDEKATAN BUSINESS MODEL CANVAS (BMC) DAN ANALISIS SWOT - Nina Hairiyah; Raden Rizki Amalia (Agroindustrial Technology, University of Trunojoyo Madura, 2021)
Maju Jaya Abadi farmer group is a farmer group engaged in the cultivation of kelulut bee in Telaga Langsat village, Takisung District, Tanah Laut Regency with Yamni Honey as its outpot product. Based on provious research, it is know that the marketing productivity of their product is still low, so it has an impact on the benefits obtained. Offorts to increase marketing productivity serving are formulated with the Business Model Canvas and SWOT analysis. The results showed that the Yamni Honey had all the building blocks in the Business Model Canvas, including the customer segments (tourists, general public and shops or pharmacies), value proposition (trademark, PIRT number, price, taste and thickness of honey), channels (private outlet , partner outlet and delivery order), costumer relationship (party or retail purchases and discounted prices), revenue stream (product marketing), key resources (facilities, human and financial), key activities (culvation, honey processing, packaging and product marketing), key partnership (government tourim office, Dekranasda, paman Adul pastry shop and Hani pharmacy), and cost structure (production cost, promotion and marketing). As for SWOT analysis, it is shown that the raw materials, production, product, price and marketing are a factor strengths, weakness, opportunities and threats to Yamni Honey marketing. Based on the analysis of the Maju Jaya Abadi farmer group are in quadrant I (growth) with a strength value of 0.39 and an opportunity of 0.18. Efforts made to improve the productivity of marketing that serves is to use SO (Strength-Oppotunity) strategy, where in marketing their product the farmer group Maju Jaya Abadi is expected to utilize the strengths they have to achieve opportunities that exist outside the product in order to increase marketing productivity from Yamni Honey.